Los hijos del trabajo : los artesanos de la ciudad de México, 1780-1853 - Perez Toledo, Sonia (Book collections on Project MUSE., 1996)
"Ground-breaking study of the artisans in Mexico during a significant period of transformation. Concludes that their numbers and their percentage of the population stayed about the same over time, but that their conditions of life and work changed significantly. Contains important statistical material useful to any scholar working on those years. Highly recommended"--Handbook of Latin American Studies, v. 58.